Effectiveness of active nasal surveillance culture for Methicillin-resistant Staphylococcus aureus in patients undergoing colorectal surgery. Issue 12 (December 2020) - Kondo, Takayuki; Okabayashi, Koji; Sugiura, Kiyoaki; Obara, Hideaki; Takeuchi, Hiroya; Wada, Norihito; Takano, Yaoko; Iwata, Satoshi; Hasegawa, Naoki; Kitagawa, Yuko
Abstract: Objective: The aim of this study was to clarify the role of Methicillin-resistant Staphylococcus aureus (MRSA) carriers in the development of surgical site infection (SSI) after colorectal surgery. Summary background data: MRSA is commonly implicated in hospital-acquired infections. Active surveillance culture (ASC) using the nasal swab test is useful to detect MRSA in surgical patients. We hypothesized that MRSA carriers would be more susceptible to SSI after colorectal surgery Methods: Patients who underwent ASC between 2010 and 2013 were included in this study. The incidence of SSI was compared between MRSA carriers and non-carriers using the chi-square test. The odds ratio for SSI was computed using logistic regression analyses. Results: Among 355 patients, 12 (3.4%) were identified as MRSA carriers and 343 as non-carriers. Of all the patients, 65 patients (18.3%) developed an SSI. Of these, 6 cases were in MRSA carriers and 59 cases were in non-carriers (p < 0.01). This meant that half of the 12 MRSA carriers developed an SSI, compared with only 17.2% of non-carriers (59 cases out of 343 patients). Therefore, MRSA carriers had a significantly higher risk of SSI (adjusted odds ratio = 4.77 [1.37 to 16.6], p = 0.01). Conclusions: Detection of MRSA via ASC is significantly associated with the development of SSI after colorectal surgery. These findings indicate that ASC for MRSA is useful to predict an SSI.